Design and Implementation of Internet Network Infrastructure Using the Network Development Life Cycle Method at SMK Rahmatullah Al-Maarif - Hartono Wijaya; M. Fawazi Hadi (Jurnal Pengabdian Masyarakat Inovatif, 2026)
The advancement of technology in the Industrial Revolution 4.0 era requires educational institutions, especially vocational schools, to have reliable internet network infrastructure to support technology-based learning. However, prior to this community service activity, SMK Rahmatullah Al-Maarif in Lombok, West Nusa Tenggara, Indonesia experienced several network problems, including slow internet connections, limited coverage areas, and inadequate network hardware, which hindered the implementation of digital learning activities. Therefore, this activity aimed to improve the school’s internet network infrastructure using the Network Development Life Cycle (NDLC) method through the stages of analysis, design, prototype simulation, implementation, monitoring, and management. Network testing was conducted using Speedtest under normal school operational conditions by measuring download speed, upload speed, and latency on wired and wireless devices. The results showed that the implemented network infrastructure achieved an average download speed of 41.55 Mbps on wired devices and 35 Mbps on wireless devices, with a latency of 34ms, indicating a stable internet connection that supports technology-based learning activities more effectively. The implementation also improved internet accessibility and network coverage across the school environment.